2020
DOI: 10.1302/2633-1462.112.bjo-2020-0166.r1
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid interleukin-6 is not superior to cell count and differential in the detection of periprosthetic joint infection

Abstract: Aims Synovial fluid white blood cell (WBC) count and percentage of polymorphonuclear cells (%PMN) are elevated at periprosthetic joint infection (PJI). Leucocytes produce different interleukins (IL), including IL-6, so we hypothesized that synovial fluid IL-6 could be a more accurate predictor of PJI than synovial fluid WBC count and %PMN. The main aim of our study was to compare the predictive performance of all three diagnostic tests in the detection of PJI. Methods Patients undergoing total hip or knee revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For our cohort the speci city of WBC count (88%) and PMN% (98%) was as high as for pH (89%), whereas the sensitivity was best for WBC count (90%), but lower for PMN% (73%) and pH (53%). However, other institutions [12] or authors [23] recommend lower cut-off values to detect low-grade infections due to the fact, that the change of synovial uid parameters depends on the virulence of bacteria [12] and may be as low as 1500 leukocytes and 65% PMN which must also be considered when interpreting synovial pH testing and the sensitivity reported here.…”
Section: Discussionmentioning
confidence: 89%
“…For our cohort the speci city of WBC count (88%) and PMN% (98%) was as high as for pH (89%), whereas the sensitivity was best for WBC count (90%), but lower for PMN% (73%) and pH (53%). However, other institutions [12] or authors [23] recommend lower cut-off values to detect low-grade infections due to the fact, that the change of synovial uid parameters depends on the virulence of bacteria [12] and may be as low as 1500 leukocytes and 65% PMN which must also be considered when interpreting synovial pH testing and the sensitivity reported here.…”
Section: Discussionmentioning
confidence: 89%
“…For both synovial fluid PCR and synovial fluid IL6, the sensitivity of each test has remained similar, but the specificity has increased compared to the results of previous meta-analyses. 5,7 the performance characteristics of each test, as well as the results of previous meta-analyses, is summarized in table v. Further to this, a previous study by mihalič et al 45 showed that synovial fluid IL6 was not superior to cell count and differential in the detection of PJi. likelihood ratio scattergram analyses (Figure 8 and Figure 9) demonstrated synovial fluid PCR and synovial fluid IL6 to be best used as confirmatory tests.…”
Section: Discussionmentioning
confidence: 90%
“…For our cohort the specificity of WBC count (88%) and PMN% (98%) was as high as for pH (89%), whereas the sensitivity was best for WBC count (90%), but lower for PMN% (73%) and pH (53%). However, other institutions [ 12 ] or authors [ 25 ] recommend lower cut-off values to detect low-grade infections due to the fact, that the change of synovial fluid parameters depends on the virulence of bacteria [ 12 ] and may be as low as 1500 leukocytes and 65% PMN which must also be considered when interpreting synovial pH testing and the sensitivity reported here.…”
Section: Discussionmentioning
confidence: 99%